Bentuk Pemenuhan Kebutuhan Anak Asuh di Lembaga Kesejahteraan Sosial Anak Al-Firdaus - Fiesta Geneoadi; Mahfudz Shidiq; Arif Arif (Electronical Journal of Social and Political Sciences (E-SOSPOL), 2023)
LKSA Al- Firdaus is an institution that provides substitute services for parents in meeting the needs of children who have an underprivileged background, do not have a complete family, neglected children and delinquent children. Referring to the conditions on the ground that all foster children do not live in the Al-Firdaus orphanage. Apart from that, regarding the physical condition of the children who looked healthy, contained even though they came from underprivileged families. This study aims to describe the form of meeting the needs of foster children at LKSA AlFirdaus. Researchers used a qualitative approach with a descriptive type of research. The informant determination technique uses purposive. Data collection techniques using non- participatory observation, semi- structured interviews, and documentation. The data analysis technique used four stages, namely data collection, data reduction, display data and conclusion drawing/ verification. In addition, the researcher used method and source triangulation techniques. The results of this study describe the form of meeting the needs provided by LKSA to their foster children. The conclusion is that the form of meeting the needs of foster children at LKSA Al- firdaus is in the form of (1) fulfilling physiological needs which include fulfilling clothing, food, health, and education (2) meeting security and safety needs (3) meeting social needs (4) meeting social needs appreciation (5) fulfillment